2020
DOI: 10.1155/2020/6263921
|View full text |Cite
|
Sign up to set email alerts
|

miR-155-5p Implicates in the Pathogenesis of Renal Fibrosis via Targeting SOCS1 and SOCS6

Abstract: Renal fibrosis is associated with the reduction in the functional renal parenchyma and in most cases progresses to end-stage kidney failure, a devastating condition that requires lifelong dialysis or kidney transplantation. However, due to the extreme complexity in the pathogenesis of renal fibrosis and our limited knowledge, therapeutic options for renal fibrosis in the clinical setting are still scarce and often ineffective. Hence, further studies on the molecular mechanisms underlying renal fibrosis are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…Of the 12 lipid species significantly up‐regulated in apical sEV derived from inflammatory versus normal PTEC, four ceramide species (Cer d18:1/16:0, Cer d18:1/20:0, Cer d18:1/22:0, Cer d18:1/24:0) have been previously reported as elevated in the urine of diabetic nephropathy patients and correlating with urinary biomarkers of renal tubular injury (e.g., N‐acetyl‐β‐D‐glucosaminidase; NAG) (Morita et al., 2020). Moreover, three of the 14 defined miRNA species significantly elevated in apical sEV derived from inflammatory PTEC (miR‐155‐5p, miR‐132‐3p, miR‐423‐5p) have been implicated in pathways of kidney injury (Lv et al., 2018; Yuan et al., 2017; Zhang et al., 2020). In particular, elevated urinary levels of miR‐155 have been reported in patients with diabetic nephropathy (Beltrami et al., 2018) and IgA nephropathy (Wang et al., 2011), whilst miR‐423 is increased in the urine of AKI patients (Ramachandran et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 12 lipid species significantly up‐regulated in apical sEV derived from inflammatory versus normal PTEC, four ceramide species (Cer d18:1/16:0, Cer d18:1/20:0, Cer d18:1/22:0, Cer d18:1/24:0) have been previously reported as elevated in the urine of diabetic nephropathy patients and correlating with urinary biomarkers of renal tubular injury (e.g., N‐acetyl‐β‐D‐glucosaminidase; NAG) (Morita et al., 2020). Moreover, three of the 14 defined miRNA species significantly elevated in apical sEV derived from inflammatory PTEC (miR‐155‐5p, miR‐132‐3p, miR‐423‐5p) have been implicated in pathways of kidney injury (Lv et al., 2018; Yuan et al., 2017; Zhang et al., 2020). In particular, elevated urinary levels of miR‐155 have been reported in patients with diabetic nephropathy (Beltrami et al., 2018) and IgA nephropathy (Wang et al., 2011), whilst miR‐423 is increased in the urine of AKI patients (Ramachandran et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-155-5p reduces the expression of MyD88 and causes the abrogation of NFκB activation. miR-155-5p is highly expressed in kidneys from renal patients and experimental obstructive renal models, promoting renal fibrosis [ 132 ]. However, the relationship between miR-155-5p and acute renal inflammation has not been reported and further studies are required.…”
Section: Regulation Of the Tlr4 Pathwaymentioning
confidence: 99%
“…Recent publications by Ye et al 2016, Chang et al 2016, Zhang et al, 2020 demonstrated that SOCS1 was the direct target of miR-155–5p by performing a luciferase reporter assay using HEK293 cells. The cells were co-transfected with the wild-type (WT) or mutated (Mut) SOCS1 luciferase reporter vector, together with miR-155 mimic and the control for 24 and 48 h. The result showed that luciferase activity was significantly inhibited in cells transfected with WT SOCS1 and miR-155 mimic, but not in cells transfected with mutation SOCS1 and miR-155 mimic [ 33 , 50 , 51 ]. Therefore, our results provide justification for further evaluation about the role of miR-155–5p in foam cell atherosclerosis by doing luciferase assay to get transcriptional activity profile of miRNA with 3′UTR of gene targets.…”
Section: Discussionmentioning
confidence: 99%